Revealed altruism - James C. Cox; Daniel Friedman; Vjollca Sadiraj (University of California, Economics Department, 2005)
This paper develops a theory of revealed preferences over one.s own and others.monetary payos. We introduce .more altruistic than.(MAT), a partial ordering over preferences, and interpret it with known parametric models. We also introduce and illustrate .more generous than. (MGT), a partial ordering over opportunity sets. Several recent discussions of altruism focus on two player extensive form games of complete information in which the .rst mover (FM) chooses a more or less generous opportunity set for the second mover (SM). Here reciprocity can be formalized as the assertion that an MGT choice by the FM will elicit MAT preferences in the SM and, fur- thermore, that the eect on preferences is stronger for acts of commision than acts of ommision by FM. We state and prove propositions on the observable consequences of these assertions. Then we test those propositions using exist- ing data from investment games with dictator controls and Stackelberg games and new data from Stackelberg mini-games.
Keywords: 330; Offenbarte Präferenzen; Altruismus; Willingness to pay; Theorie